2022
DOI: 10.1136/bjo-2022-321621
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic change in retinal nerve fibre layer thickness from 30 to 60 weeks postmenstrual age in preterm infants

Abstract: Background/AimsThe optic nerve development during the critical postnatal weeks of preterm infants is unclear. We aimed to investigate the change of retinal nerve fibre layer (RNFL) in preterm infants.MethodsWe used an investigational handheld optical coherence tomography (OCT) system to serially image awake preterm infants between 30 and 60 weeks postmenstrual age (PMA) at the bedside. We assessed RNFL thickness in the papillomacular bundle and nasal macular ganglion cell layer+inner plexiform layer (GCL+IPL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…RNFL thickness in preterm infants follows a biphasic pattern of change between 30 and 60 weeks PMA. In BabySTEPS, we found that the RNFL thickness increases at 1.8 µm/week from 30 to 37.8 weeks PMA and then decreases at −0.3 µm/week from 37.8 to weeks PMA ( 41 ). We did not find an association between RNFL thickness and macular edema in either BabySTEPS or our earlier report with Rothman et al ( 20 , 41 ).…”
Section: Optic Nerve and Retinal Nerve Fiber Layermentioning
confidence: 87%
See 1 more Smart Citation
“…RNFL thickness in preterm infants follows a biphasic pattern of change between 30 and 60 weeks PMA. In BabySTEPS, we found that the RNFL thickness increases at 1.8 µm/week from 30 to 37.8 weeks PMA and then decreases at −0.3 µm/week from 37.8 to weeks PMA ( 41 ). We did not find an association between RNFL thickness and macular edema in either BabySTEPS or our earlier report with Rothman et al ( 20 , 41 ).…”
Section: Optic Nerve and Retinal Nerve Fiber Layermentioning
confidence: 87%
“…In BabySTEPS, we found that the RNFL thickness increases at 1.8 µm/week from 30 to 37.8 weeks PMA and then decreases at −0.3 µm/week from 37.8 to weeks PMA ( 41 ). We did not find an association between RNFL thickness and macular edema in either BabySTEPS or our earlier report with Rothman et al ( 20 , 41 ). This understanding of the biphasic thickness change may be useful when evaluating the longitudinal impact of diseases such as ROP and interventions such as ROP treatment on infant retinal development.…”
Section: Optic Nerve and Retinal Nerve Fiber Layermentioning
confidence: 87%
“… 12 , 17 , 18 Both RNFL thickness and axial length undergo rapid growth until approximately 38 to 42 weeks or around the time an infant would be considered full-term, after which grow slows dramatically. 6 , 7 , 8 Similarly, the retinal vasculature grows rapidly until 36 weeks nasally and 40 weeks temporally, at which time the retina is considered fully vascularized. The signaling molecules underlying this abrupt TP near term followed by slower growth rate post 40 weeks remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously applied this segmented mixed model to analyze the change of RNFL thickness. 6 Statistical significance was defined as 2-sided P < 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation